Snakes and Ladders Media to Improve Learning Outcomes in Pancasila Education for Fourth Grade Elementary School Students - Puji Rahayu, Vefta; Dwi Prasetyaningtyas, Fitria (Jurnal Pendidikan Indonesia, 2025)
Implementing learning is still not optimal when using learning media, so student learning outcomes still need to be higher. This research aims to develop snakes and Ladders learning media to improve learning outcomes in attitude and behavior material that reflects the practice of Pancasila in the social life of class IV students. This type of research is development research with the ADDIE model. The subjects of this research are learning materials experts and learning media experts. The test subjects were teachers and class IV elementary school students, totaling 27 students. The methods used to collect data are interviews, observation, questionnaires, documentation, and tests. Data collection instruments are question sheets, interview guidelines, observation sheets, questionnaire sheets, documentation, and test questions. Data analysis techniques include quantitative, qualitative, and inferential statistics. The research results were validation results from media experts, namely 94%, and material experts, 84%, so learning media received very decent qualifications. The results of the t-test in the small group and large group showed a significant difference in pretest and post-test scores. The results of the N-gain test show that student learning outcomes have increased after carrying out learning assisted by the Snakes and Ladders game media. It was concluded that the Snakes and Ladders learning media could improve the learning outcomes of elementary school students.